Vận dụng mô hình branded house trong xây dựng thương hiệu đại học theo khung phân tích brand equity: Nghiên cứu thực trạng tại Trường Đại học Tân Trào - Hoàng Thị Ngọc Hà, Hoàng Thị Ngọc Hà; Trần Vũ Phương, Trần Vũ Phương; Triệu Thị Kim Cúc, Triệu Thị Kim Cúc (Tạp chí Giáo dục, 2026)
In the context of Vietnamese higher education increasingly promoting autonomy and competition, branding has become a strategic resource for the sustainable development of local universities such as Tan Trao University. However, the University’s branding activities still lack an appropriate theoretical framework and analytical approach. This study aims to clarify the theoretical foundations and propose an analytical framework applying the Branded House model to university branding. A mixed-methods approach was employed, combining document analysis and a questionnaire survey of students, lecturers, and administrators; the data were analyzed using descriptive statistics. The findings indicate that the component groups were rated from moderate to fairly good; among them, strategic and visual identity were evaluated more positively than communication and behavioral identity. These results reflect the current situation and suggest areas that need further improvement in order to enhance the consistency of the university brand. The study contributes to extending the Branded House approach to the field of university brand management at Tan Trao University in particular, while also providing a useful reference tool for future research, evaluation, and strategic brand planning in higher education institutions.